2009
DOI: 10.1080/10739680902832795
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Impairs Endothelial Function but not Adrenergic Reactivity or Vascular Structure in Fructose‐fed Rats

Abstract: Obesity and diabetes are major risk factors for the development of vascular disease in the lower limbs. Previous studies have demonstrated reduced nitric oxide (NO)-mediated vasodilation, increased adrenergic constriction and inward, atrophic remodeling in the limb circulation of obese Zucker rats but the component of the “metabolic syndrome” driving these changes is unclear. Because insulin resistance precedes the state of frank diabetes, the current study hypothesized that insulin resistance independent of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…These data are consistent with our recent findings where 10 weeks of high fat diet treatment also increased plasma insulin levels in WKY and SHR [8]. Insulin resistance has been shown to contribute to the development of endothelial dysfunction [24, 40] as high insulin levels induce renal hemodynamic changes, glomerular hypertrophy, and mesangial cell proliferation [41, 42]. Together, these data suggest that high fat diet induced insulin resistance and ANG hypertension did not potentiate this effect.…”
Section: Discussionsupporting
confidence: 93%
“…These data are consistent with our recent findings where 10 weeks of high fat diet treatment also increased plasma insulin levels in WKY and SHR [8]. Insulin resistance has been shown to contribute to the development of endothelial dysfunction [24, 40] as high insulin levels induce renal hemodynamic changes, glomerular hypertrophy, and mesangial cell proliferation [41, 42]. Together, these data suggest that high fat diet induced insulin resistance and ANG hypertension did not potentiate this effect.…”
Section: Discussionsupporting
confidence: 93%
“…; Romanko et al. ) suggesting that findings in that model may reflect the artificial processes involved in its generation rather than metabolic dysfunction as manifest by normal disease processes. While it is likely simplistic to assume the hypertension is the sole drive of vascular dysfunction in obesity, this study adds to a growing body of evidence that it may be the primary one.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that FRD promotes decreases in endothelial NO production [9] and vasorelaxation [10,11] as well as impaired insulin-induced vasodilation [9]. Further, the FRD model is also useful to test the effects of different preventive strategies aimed at decreasing MS vascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%